The Omarska memorial project as an example of how transitional justice interventions can produce hidden harms - Sivac-Bryant, Sebina (International journal of transitional justice, 2015)
This article uses the example of a failed project, whose aim was to achieve consensus around constructing a memorial at the former Omarska camp in Bosnia and Herzegovina, to illustrate some of the dangers of transitional justice interventions involving victims of dislocation and violence, as well as the potential for hidden harms. It is based on nine years of ethnographic research into a small returnee community in Kozarac, in the municipality of Prijedor. Well-intentioned as the project undoubtedly was, it had unintended consequences for the social relations of the local community. Like other internationally led initiatives, it can be argued that it helped reinforce a victim-perpetrator dynamic that prevented rather than assisted progress. Although we cannot draw too many conclusions from one project, the issues highlighted by this initiative have been echoed on a smaller scale in much of the international involvement of transitional justice scholars and activists in the town since then.